Theta-nested gamma oscillations balance prediction and vigilance in spatial navigation - Kwan Tung Li; Ziqun Wang; Pulin Gong; Dongping Yang (Proceedings of the National Academy of Sciences, 2025)
Recent experimental findings challenge the traditional belief that vigilance is solely attributed to the sensorimotor system, suggesting instead that hippocampal activity, coupled with locomotor processes, enhances environmental sampling and planning. Here, we propose that hippocampal theta-nested gamma oscillations (TGOs), widely observed in experiments, play essential roles in both prediction and vigilance, in terms of recalling reward sites and avoiding unexpected dangers through synfire chains (SFCs). Despite the recognized importance of TGOs in navigation, their precise functional roles remain unclear. By building a biologically plausible spiking neuronal network model and reproducing experimental results, we leverage SFC properties-length and separation-to reveal that the positive correlation between theta frequency and motion velocity optimally balances planning for predictable events and staying alert to unexpected ones. Based on this adaptive mechanism, we further explain the distinct functional contributions of TGOs consistent with experimental findings: Theta oscillations facilitate self-location awareness, gamma oscillations enhance predictive capabilities, and their coupling ensures sufficient time windows for prediction. Our study provides insights into the functional roles of TGOs in the hippocampus, highlighting their importance in achieving both planning and vigilance during goal-directed navigation.